ANALISIS BUKU AJAR BAHASA ARAB SISWA KELAS VIII MTs/SMP ISLAM DALAM PERSEPEKTIF GENDER - Muh Sabilar Rosyad (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
Abstrak: In the process of teaching and learning Arabic, Textbooks are present in perfecting the trilogy of learning elements, including teachers, students and the teaching material itself. However, in the process of preparing and redesigning these materials, it was still found to be more or less a gender bias that was the result of community reconstruction both culturally and systemically. Therefore, this study tries to dig with a knife analysis related to some forms of gender habits in the sample of Arabic textbooks used at the level of Madrasah Tsanawiyah or Islamic Middle School. Based on the above topic, this research uses descriptive analysis method with the type of library research. The conclusions resulting from him are: 1. Gender bias in the sample is expressed in the form of drawings and writing with the discovery of gender inequality that can lead to injustice. The roles of men and women have not been balanced. Men still occupy a central role that causes women to be prioritized. 2. The discovery of several forms of discrimination, including: Stereotype, Subordering, and Double Burden.Keywords: Arabic Language, Gender.